Analysis of Internal Financial Factors Affecting Stock Prices in Food and Beverage Companies in Indonesia - Rachmawinda Alfioni Azra; Yessi Monalisa Saruksuk; Eka Yosi Indriyani; Farah Margaretha Leon (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to examine internal financial factors with financial ratios beta value, acid-test ratio, total assets, financial leverage, and operating profit margin on stock prices. The data collection technique uses secondary data from 14 food and beverage companies with IPOs listed on the IDX for 2012-2019. Data analysis was performed using a panel data regression test with Eviews 9.0 application. The results showed that beta value, financial leverage, operating profit margin had no significant effect on stock prices. However, the acid-test ratio had a significant adverse impact on stock prices, and total assets significantly positively affected stock prices. Thus, the study results can be used as a reference for companies in maintaining and increasing their stock price from financial factors that can influence it. It is also helpful for investors as a consideration in choosing companies to invest in. The update in the research lies in the way the data is tested, namely using a panel data regression test with a sampling period of 8 years (2012-2019 period).